(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Carbon nanotubes (CNTs) doped nematic liquid crystal (NLC) mixture of varying concentrations of CNTs in 0.0, 0.2 and0.5 wt./wt.% ratios have been prepared and studied. The effect of electric field on current behavior and optical propertiesin pure NLC and CNTs-NLC mixtures has been investigated. Dispersion of CNTs in NLC mixture increases the currentnearly 3 times. The lower concentration of CNTs leads to better optical responses